دور التمكين في إدارة الكفاءات: دراسة حالة مؤسسة موبيليس الشلف - قوادرى، فضيلة معمر (جامعة محمد بوضياف المسيلة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2020)
تمثل الهدف من الدراسة الحالية في بحث دور التمكين في إدارة الكفاءات بمؤسسة موبيليس بالشلف، ولهذا الغرض تم توزيع استبيان على عشوائية بلغت (70) عاملا. وقد تم استخدام برنامج (SPSS) في التحليل. وتم التوصل إلى النتائج التالية: لا توجد فروق ذات دلالة إحصائية في إدراك العاملين لمتغيرات الدراسة المتمثلة في: التمكين (المشاركة، المعرفة، حرية التصرف والاستقلالية)، وإدارة الكفاءات تعزى للفئة الوظيفية، بينما توجد فروق ذات دلالة إحصائية في إدراك العاملين هذه المتغيرات تعزى للخبرة. وكان مستوى استجابة أفراد عينة الدراسة للتمكين وإدارة الكفاءات منخفضا. وتم التوصل إلى وجود علاقة ارتباط متوسطة بلغت (0,665) بين التمكين وإدارة الكفاءات من وجهة نظر أفراد عينة الدراسة.
The aim of the current study was to examine the role of empowerment in the competency management at Mobilis Company Chlef, For this purpose, a questionnaire was distributed to a random sample of 70 workers. SPSS program has been used for analysis. The following results were obtained: no statistically significant differences in the perception of employees variables of the study of: empowerment (participation, knowledge, freedom and autonomy), and competency management were attributed to the category of job, while there are statistically significant differences in the perception of employees of these variables is attributable to the experience. The level of responsiveness of sample personnel to empowerment and competency management was low. An average correlation (0.665) was found between empowerment and competency management from the perspective of sample members.
Keywords: إدارة الموارد البشرية -- التمكين الإداري -- إدارة الكفاءات -- الرضا الوظيفي